1992
DOI: 10.1113/jphysiol.1992.sp019076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the stimulation pattern on the fatigue of single motor units in adult cats.

Abstract: SUMMARY1. The main purpose of this study was to examine the effects of two subtly different stimulus patterns on the force developed by fast-twitch, fatiguable motor units in a cat hindlimb muscle during control (pre-fatigue) and fatiguing contractions.2. The peak force and the force-time integral responses of nineteen high fatigue (FF) and three intermediate fatigue (FI) motor units of the tibialis posterior muscle in five deeply anaesthetized adult cats were measured at selected times during the course of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
90
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 45 publications
10
90
0
Order By: Relevance
“…The maximal rate of force development is obtained at stimulation frequencies much higher than needed for maximal isometric force production (Buller & Lewis, 1965;Bevan, Laouris, Reinking & Stuart, 1992). In dynamic contractions, stimulation frequencies are often used which elicit the maximal rate of isometric force development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The maximal rate of force development is obtained at stimulation frequencies much higher than needed for maximal isometric force production (Buller & Lewis, 1965;Bevan, Laouris, Reinking & Stuart, 1992). In dynamic contractions, stimulation frequencies are often used which elicit the maximal rate of isometric force development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The catch-like property, later described for mammalian muscle, refers to the enhancement of force from a muscle caused by a brief high-frequency train added to a low-frequency background. 2,6,26 Burke and colleagues 6 found that when two pulses were delivered closely (10 ms), they induced a nonlinear summation that often exceeded what would have developed if two twitches were merely summed individually. Subsequently, stimulation trains with an initial highfrequency burst (variable-frequency stimulation) were found to augment force in human whole muscle 5 and paralyzed muscle.…”
Section: Catch-like Property Of Paralyzed Musclementioning
confidence: 99%
“…This phenomenon was later confirmed by various researchers and is now referred to as the "catchlike" property of muscle (2,3,23,24). Bevan and colleagues reported that when the first two stimuli were delivered at an instantaneous frequency of 100 Hz, followed by a stimulus train at 20 Hz, catchlike-inducing stimulation produced higher forces and better force maintenance compared with constant frequency stimulation in the fast motor units of cats (2). From these studies, there is a possibility that the catchlike-inducing intermittent stimulation of whole skeletal muscle can reduce muscle fatigue rather than constant frequency stimulation.…”
mentioning
confidence: 69%
“…Burke and colleagues applied a single electrical stimulation of 100 Hz at the start of low-frequency stimulation of excised feline muscles, and reported increased and sustained muscle force for the first time (8). This phenomenon was later confirmed by various researchers and is now referred to as the "catchlike" property of muscle (2,3,23,24). Bevan and colleagues reported that when the first two stimuli were delivered at an instantaneous frequency of 100 Hz, followed by a stimulus train at 20 Hz, catchlike-inducing stimulation produced higher forces and better force maintenance compared with constant frequency stimulation in the fast motor units of cats (2).…”
mentioning
confidence: 91%